Changes in the Bacterial Diversity of Human Milk during Late Lactation Period (Weeks 21 to 48) - Wendy Marin-Gómez; Mᵃ José Grande; Rubén Pérez-Pulido; Antonio Galvez; Rosario Lucas (Foods, 2020)
Breast milk from a single mother was collected during a 28-week lactation period. Bacterial diversity was studied by amplicon sequencing analysis of the V3-V4 variable region of the 16S rRNA gene. Firmicutes and Proteobacteria were the main phyla detected in the milk samples, followed by Actinobacteria and Bacteroidetes. The proportion of Firmicutes to Proteobacteria changed considerably depending on the sampling week. A total of 411 genera or higher taxons were detected in the set of samples. Genus Streptococcus was detected during the 28-week sampling period, at relative abundances between 2.0% and 68.8%, and it was the most abundant group in 14 of the samples. Carnobacterium and Lactobacillus had low relative abundances. At the genus level, bacterial diversity changed considerably at certain weeks within the studied period. The weeks or periods with lowest relative abundance of Streptococcus had more diverse bacterial compositions including genera belonging to Proteobacteria that were poorly represented in the rest of the samples.